Representasi dan Interpretasi Kaomoji (Emotikon Bahasa Jepang) melalui pendekatan semiotika Pierce - Tresnasari, Ningrum (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 1 No 1 (2019)DO - 10.24843/JS.2019.v01.i01.p02, 2019)
Semiotik is one of the studies in linguistics that aims to explain how signs or symbols can represent objects, ideas, conditions, situations, feelings, and conditions outside the symbol itself . This study aims to discuss the use of symbols in the form of Japanese emoticons (kaomoji) in explaining things that are not represented because of limitations in tone, voice, and expression when communicating in a non-verbal way . By using Pierce's semiotic theory, this study also looks at how culture becomes the basis of the formation of meaning in a sign or symbol on kaomoji . In other words, kaomoji has a meaning that aims to emphasize expression, reinforce emotions, and a form of positive appreciation . Besides that, the very varied and creative kaomoji illustrates that Japanese people are very expressive and full of enthusiasm . Keywords : Kaomoji , Non Verbal Communication, Symbol dan Meaning